Narrowband imaging with near‐focus magnification for discriminating the gastric tumor margin before endoscopic resection: A prospective randomized multicenter trial. Issue 11 (16th June 2020) - Kim, Jung‐Wook; Jung, Yunho; Jang, Jae‐Young; Kim, Gwang Ha; Bang, Byoung Wook; Park, Jun Chul; Choi, Hyuk Soon; Cho, Jun‐Hyung; ,
Abstract: Background and Aim: This study investigated the usefulness of near‐focus narrowband imaging (NF‐NBI) for determining gastric tumor margins compared with indigo carmine chromoendoscopy (ICC) before endoscopic submucosal dissection (ESD). Methods: This prospective randomized controlled trial was conducted at seven teaching hospitals in Korea. Patients with gastric adenoma or differentiated adenocarcinoma undergoing ESD were enrolled and randomly assigned to the NF‐NBI or ICC group. A marking dot was placed on the most proximal margin of the tumor before ESD. The primary endpoint was delineation accuracy, which was defined as presence of marking dots within 1 mm of the tumor margin under microscopic observation. Results: A total of 200 patients in the NF‐NBI group and 195 patients in the ICC group were included. The delineation accuracy rate was 84.5% in the NF‐NBI group and 81.0% in the ICC group ( P = 0.44). However, the distance from the marking dot to the margin of the tumor was significantly shorter in the NF‐NBI group than in the ICC group (0.8 ± 0.8 vs 1.2 ± 1.3 mm, P < 0.01). Even after adjustment of other clinicopathological factors that are associated with difficulty of tumor delineation, NF‐NBI did not show significant association with accurate delineation (odds ratio of 0.86, P = 0.60). Conclusions: This prospective multicenter study showed that NF‐NBI is not superior to ICC in terms of accurately delineating gastric tumors (NCT02661945).